2022
DOI: 10.3390/cancers14092115
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in Pancreatic Cancer: Biologic Functions, Mechanisms, and Clinical Significance

Abstract: Despite tremendous efforts devoted to research in pancreatic cancer (PC), the mechanism underlying the tumorigenesis and progression of PC is still not completely clear. Additionally, ideal biomarkers and satisfactory therapeutic strategies for clinical application in PC are still lacking. Accumulating evidence suggests that long non-coding RNAs (lncRNAs) might participate in the pathogenesis of diverse cancers, including PC. The abnormal expression of lncRNAs in PC is considered a vital factor during tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 258 publications
0
12
0
Order By: Relevance
“…Most lncRNAs are transcriptionally regulated by RNA polymerase II (Pol II), demanding the insertion of a 3’ end poly (A) tail and a 5’ end m7G cap [ 18 , 19 ]. Most lncRNAs are exported and localized in the cytoplasm, except a small number is kept in the nucleus [ 20 ]. Due to the limited number of exons contained in the sequence, the export of lncRNAs mainly depends on the nuclear RNA export factor 1 (NXF1) pathway [ 21 ].…”
Section: Biogenesis and The Mode Of Action Of Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Most lncRNAs are transcriptionally regulated by RNA polymerase II (Pol II), demanding the insertion of a 3’ end poly (A) tail and a 5’ end m7G cap [ 18 , 19 ]. Most lncRNAs are exported and localized in the cytoplasm, except a small number is kept in the nucleus [ 20 ]. Due to the limited number of exons contained in the sequence, the export of lncRNAs mainly depends on the nuclear RNA export factor 1 (NXF1) pathway [ 21 ].…”
Section: Biogenesis and The Mode Of Action Of Lncrnasmentioning
confidence: 99%
“…Due to the limited number of exons contained in the sequence, the export of lncRNAs mainly depends on the nuclear RNA export factor 1 (NXF1) pathway [ 21 ]. The lncRNAs can exist in various forms and perform appropriate activities once they enter the cytoplasm [ 20 ]. Previous studies have confirmed that the mode of action of lncRNAs can be divided into four categories: signal, decoy, guide, and scaffold [ 22 , 23 ] ( Figure 1 ).…”
Section: Biogenesis and The Mode Of Action Of Lncrnasmentioning
confidence: 99%
“…However, >80% of patients are diagnosed with PC at an advanced stage, making them unsuitable for surgical treatment 3 . Some molecules have become potential biomarkers for the diagnosis and prognosis of PC 4–6 . For example, the concentrations of serum biomolecules CEA, CA 19‐9, and CA 242 have reliable sensitivity and specificity as biomarkers for the early diagnosis and prognosis of PC 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concentrations of serum biomolecules CEA, CA 19‐9, and CA 242 have reliable sensitivity and specificity as biomarkers for the early diagnosis and prognosis of PC 4 . It was reported that various long noncoding RNAs (lncRNAs) were aberrantly expressed in PC and played crucial roles in this disease 5 . However, the underlying mechanisms need further enrichment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation